Effect Of Islamic Financial Literacy, Religiosity, And Lifestyle On Decision To Use Islamic Bank Products For Millennial Generation In Greater Jakarta - Reny Fitriana Kaban; Muhammad Guntur (Management Research Studies Journal, 2021)
This study aims to analyze the effect of Islamic financial literacy, religiosity, and lifestyle on the decision to use Islamic bank products for the millennial generation in Greater Jakarta. The data in this research were obtained by distributing questionnaires that consist of 100 Islamic bank customers as samples and using the purposive sampling technique. Partial Least Square was used as the method of data analysis. The results indicated that Islamic financial literacy, religiosity, and lifestyle have effects on the decision to use Islamic bank products in the Millennial generation. It is suggested for Islamic banks to continue the socialization of Islamic financial literacy to gather more Islamic bank customers. In addition, Islamic banks also need to develop their systems and products that apply to sharia principles and the millennial lifestyle as well.